Parental income, child labour, and human capital accumulation: evidence from trade liberalisation in India. Issue 8 (17th November 2018) - Ajefu, Joseph Boniface
ABSTRACT: This article examines whether parental income affects decisions on children's human capital investment and labour market participation. India's sudden and unanticipated trade liberalisation was a national policy that created an exogenous variation in industry-specific tariff rates over time. The policy consequently led to variation in workers' earnings according to their industrial affiliations. The disparity in earnings across industries provides a good setting for identifying the causal effect of parents' income on child's labour and schooling, using an instrumental variables approach. The study finds a positive effect of parents' income on children's schooling but a negative effect on children's work. The magnitude of effect, however, is higher for girls compared to boys.